Stage productions Parsifals of Richard Wagner at The Festival in Bayreuth: From secularism to postsecularism = Inscenizacje Parsifala Richarda Wagnera na Festiwalu w Bayreuth. Od sekularyzmu do postsekularyzmu - Kaczmarek, Jerzy (Przegla̜d religioznawczy, 2018)
In this article, I would like to analyse two stage productions Parsifals of Richard Wagner at the Festival in Bayreuth. The first production from the years 2008-2012 is made by Stefan Herheim and has in the center the problems of history, politics and psychoanalysis. The second production from the years 2016-2019 is made by Uwe Eric Laufenberg and has in the center the problems of religions and faith. The both productions can be indicators for the processes of secularism and postsecularism in the contemporary world and I would like to show that we can observe this processes also in art.